2019
DOI: 10.1002/gps.5061
|View full text |Cite
|
Sign up to set email alerts
|

Associations between handgrip strength and mild cognitive impairment in middle‐aged and older adults in six low‐ and middle‐income countries

Abstract: Objectives A number of small‐scale, single‐country studies have suggested that muscular weakness may be a biomarker for cognitive health, mild cognitive impairment (MCI), and dementia. However, multinational, representative studies are lacking, particularly from low‐ and middle‐income countries (LMICs). Thus, we assessed the association between muscular strength (measured by maximal handgrip) and MCI in six LMICs (China, Ghana, India, Mexico, Russia, and South Africa), using nationally representative data. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 56 publications
(82 reference statements)
3
35
0
3
Order By: Relevance
“…An insufficient duration per session may be the factor for the differing results, which suggests that resistance training with an adequate duration per session may be more effective. A cross-sectional survey also revealed a relationship between muscle strength and the incidence of MCI; in other words, resistance training that increases muscle strength may prevent MCI [25]. Another study shows that the potential of resistance training to improve general cognitive function in MCI patients may be associated with a high level of insulin-like growth factor-1, which promotes neuronal growth, survival and differentiation and improves cognitive performance [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An insufficient duration per session may be the factor for the differing results, which suggests that resistance training with an adequate duration per session may be more effective. A cross-sectional survey also revealed a relationship between muscle strength and the incidence of MCI; in other words, resistance training that increases muscle strength may prevent MCI [25]. Another study shows that the potential of resistance training to improve general cognitive function in MCI patients may be associated with a high level of insulin-like growth factor-1, which promotes neuronal growth, survival and differentiation and improves cognitive performance [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have linked resistance training with improved cognition in MCI patients. A recent cross-sectional study suggests that lower muscle strength may be associated with the incidence of MCI and that resistance training to enhance muscle strength can reduce the incidence of MCI [25]. Previous reviews have also shown that resistance training is good for cognition in the elderly [26].…”
Section: Introductionmentioning
confidence: 99%
“…51 Vancampfort et al recently reported that among middle-aged and older adults, weak grip strength was associated with increased odds of having mild cognitive impairment. 52 Others have shown a correlation between grip strength and the Mini-Mental State Examination scores of geriatric inpatients, 53 information processing speed and executive functioning of patients attending a memory clinic, 54 Stroop Task and 6item Cognitive Impairment Test scores of physically active adults, 55 visual memory,and reaction time of patients with schizophrenia, 56 and Animal Fluency Test and Digital Symbol Substitution Test scores of cancer survivors. 57 A link between grip strength and depression has been demonstrated among residents of 6 low and middle income countries 58 as well as Brazil 59 and Korea.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 99%
“…48 Another cross-sectional study of 32,715 adults aged 62.0 ± 15.6 years revealed that weakness was associated with 1.41 greater odds (p < 0.05) for mild cognitive impairment. 49 Although crosssectional study designs provide insights into the association of HGS and cognitive impairment, longitudinal study designs will help to reveal temporal inferences.…”
Section: Hgs and Neural Morbiditiesmentioning
confidence: 99%